The role of dutasteride in reducing complications of transurethral resection of prostate - Shyamal Shah; P. Periasamy (Al Ameen Journal of Medical Sciences, 2025)
Purpose: To evaluate the superiority of dutasteride over a placebo in patients having their prostate removed during transurethral resection for benign prostate hyperplasia. Material and Methods: The study included a total of 30 patients, with 15 patients allocated to each group (group placebo and group B- Dutasteride). Group A received a placebo for two weeks before surgery and two weeks after surgery and group B received dutasteride respective time slots. Result: TURP tissue weight among the placebo and Dutasteride groups, the mean resected tissue weights were 25.86 and 29.6 grams, respectively. The study also examined micro vessel density (MVD) in the suburethral portion of prostatic tissue, which was found to be highest in the placebo group (22.05) compared to the Dutasteride (16.2) group. In the hyperplastic portion of prostatic tissue, MVD was slightly higher in the placebo group (16.04) than in the Dutasteride (14.86) group. Conclusions: Preoperative treatment with dutasteride for two weeks before TURP reduces surgical bleeding and length of hospitalization after TURP. This pre-treatment can be used to decrease surgical bleeding associated with the TURP.